2005
DOI: 10.1051/forest:2004095
|View full text |Cite
|
Sign up to set email alerts
|

Effect of defoliation by Thaumetopoea pityocampa (Den. & Schiff.) (Lepidoptera: Thaumetopoeidae) on annual diameter increment of Pinus brutia Ten. in Turkey

Abstract: -In this study, the influence of defoliation by pine processionary moth, Thaumetopoea pityocampa (Den. & Schiff.) (Lepidoptera: Thaumetopoeidae) on the annual diameter increment of Turkish Calabrian pine, Pinus brutia Ten. in Kahramanmaras province, Turkey, was investigated. The study was carried out between 1995 and 1998. During the four years, the defoliation of pine processionary moth caused a significant decrease (average 21% for four years, P < 0.05) in the annual diameter increment with respect to contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
37
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 10 publications
(9 reference statements)
2
37
0
Order By: Relevance
“…In spite of the capability of defoliated trees to refoliate and survive, the effects of defoliation are very significant (Fratian 1973) with losses in volume, radial growth (Carus 2004, Kanat et al 2005, Laurent-Hervouet 1986 and biomass pro duction (Markalas 1998). Kanat et al 2005 reported a significant decrease (average 21% over four years) on annual diameter incre ment of Pinus brutia in Turkey while Carus (2004) identified growth reductions on radial height and volume on P. brutia after an out break of T. pityocampa. Cadahia & Insua (1970) identified a decrease in wood volume increment of 14-33% in young P. radiata as well as losses in tree volume, while Bouchon & Toth (1971) reported that T. pityocampa attack was responsible for an about 45% volume decrease over a 50 year period.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…In spite of the capability of defoliated trees to refoliate and survive, the effects of defoliation are very significant (Fratian 1973) with losses in volume, radial growth (Carus 2004, Kanat et al 2005, Laurent-Hervouet 1986 and biomass pro duction (Markalas 1998). Kanat et al 2005 reported a significant decrease (average 21% over four years) on annual diameter incre ment of Pinus brutia in Turkey while Carus (2004) identified growth reductions on radial height and volume on P. brutia after an out break of T. pityocampa. Cadahia & Insua (1970) identified a decrease in wood volume increment of 14-33% in young P. radiata as well as losses in tree volume, while Bouchon & Toth (1971) reported that T. pityocampa attack was responsible for an about 45% volume decrease over a 50 year period.…”
Section: Introductionmentioning
confidence: 99%
“…Defoliation removes both photosynthetic material and sites where chemicals such as growth hormones are pro duced, affecting many vital functions (Carus 2004). It is well known that in adult trees de foliation, though repeated over consecutive years, seldom causes death (Ruperez 1956, Kailadis 1962), but increases susceptibility to sanitary problems such as pine weevils and bark beetle attack (Kanat et al 2005, Markalas 1998). In spite of the capability of defoliated trees to refoliate and survive, the effects of defoliation are very significant (Fratian 1973) with losses in volume, radial growth (Carus 2004, Kanat et al 2005, Laurent-Hervouet 1986 and biomass pro duction (Markalas 1998).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations